Computational fluid dynamics and particle image velocimetry assisted design tools for a new generation of trochoidal gear pumps. (26th June 2015) - Garcia-Vilchez, M; Gamez-Montero, PJ; Codina, E; Castilla, R; Raush, G; Freire, J; Río, C
Trochoidal gear pumps produce significant flow pulsations that result in pressure pulsations, which interact with the system where they are connected, shortening the life of both the pump and circuit components. The complicated aspects of the operation of a gerotor pump make computational fluid dynamics the proper tool for modelling and simulating its flow characteristics. A three-dimensional model with deforming mesh computational fluid dynamics is presented, including the effects of the manufacturing tolerance and the leakage inside the pump. A new boundary condition is created for the simulation of the solid contact in the interteeth radial clearance. The experimental study of the pump is carried out by means of time-resolved particle image velocimetry, and results are qualitatively evaluated, thanks to the numerical simulation results. Time-resolved particle image velocimetry is developed in order to adapt it to the gerotor pump, and it is proved to be a feasible alternative to obtain the instantaneous flow of the pump in a direct mode, which would allow the determination of geometries that minimize the non-desired flow pulsations. Thus, a new methodology involving computational fluid dynamics and time-resolved particle image velocimetry is presented, which allows the obtaining of the instantaneous flow of the pump in a direct mode without altering its behaviour significantly.